The value of active politicians on supervisory boards: evidence from the Berlin stock exchange and the parliament in interwar Germany. Issue 1 (2nd January 2019) - Lehmann-Hasemeyer, Sibylle; Opitz, Alexander
ABSTRACT: We provide the first overview over all political connections of firms via current Members of Parliament on supervisory boards and board of directors listed on the Berlin stock exchange in the 1920s. In contrast to anecdotal evidence, which suggest that political connections were expected to have a positive effect on firms' performance, an event study based on the election in December 1924 and May 1928 shows only little evidence that a political connection via a newly elected or re-elected politician generated value. These results complement previous research emphasising that political connections might have mattered less in democracies.